DEVELOPING DIGITAL PICTURE STORY BOOK TEACHING MATERIALS BASED ON MALUKU REGIONAL FOLKTALES BASED ON SEA-ISLAND FOR GRADE VIII MIDDLE SCHOOL STUDENTS IN AMBON CITY - Jeny Lekatompessy; Marcy S Ferdinandus; Felicia M Lekatompessy (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2023)
The purpose of developing teaching materials for books in English is essential to improve English language skills and maintain, study, introduce, and preserve regional folklore in the marine island environment as well as the culture and potential of the Maluku region. This research employed Research and Developmet (R and D) according Borg and Gal. Research data for English teaching materials are grouped into two types of data, quantitative data, and qualitative data. Data was obtained through the distribution of questionnaires amd interview). The results show that, the expert validation said that the initial product development of teaching materials was good but still needed to be revised before being implemented in small group and field trials. The initial product development of Diglot Picture Storybook teaching materials was good but need to insert listening activities in the Listening Skill section.